Pengaruh Soft skill terhadap Kesiapan Menjadi Guru Pada Mahasiswa Program Studi Pendidikan Ekonomi FKIP ULM - Roofiq, Muhammad; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah; Nor, Baseran (Universitas Negeri Surabaya, 2024)
Teacher students as prospective teachers must have teaching skills as preparation to become teachers. Apart from teaching skills, readiness to become a teacher is also influenced by the soft skills possessed by students. The aim of this research is to find out whether soft skills have a significant influence on readiness to become a teacher. The type of research used is associative quantitative research. The sample in this study was 109 which was collected using random sampling. Analysis of the data used in this research uses prerequisite analysis tests with normality tests and linearity tests, simple linear regression tests, and determinant coefficients (R2). The results of the research show that there is a positive and significant influence of the soft skill variable on the readiness to become teachers in study program students. economic education FKIP ULM.